STUDENT CONSUMER PATTERNS IN THE SOCIAL MEDIA ERA: OBSERVATIONAL STUDY IN THE POST-PANDEMIC ECONOMIC CONTEXT - Edi Susanto; Syafrinadina (Indragiri Research Center (ingreat), 2024)
This study aims to describe student consumption patterns formed through interactions with social media amidst post-pandemic economic uncertainty. Using a qualitative approach and non-participatory observation and documentation methods, this study explores symbolic, impulsive, and emotional consumption tendencies that emerge in students' daily lives. Observations indicate that students are actively exposed to social media content such ashaul, unboxing, and product review, which shapes perceptions of needs and encourages purchases that are not always based on real needs. Furthermore, digital social pressures reinforce consumer impulses to follow trends and build self-image in the digital space. The lack of financial records and consumption reflection indicates low financial awareness. Therefore, a contextual and adaptive consumer literacy approach to the dynamics of the younger generation's digital lifestyle is needed. This research contributes to a critical understanding of college students' consumer behavior and the importance of financial education relevant to their social realities.